HBsAg seroclearance after nucleoside analogue therapy in patients with chronic hepatitis B: clinical outcomes and durability. Issue 8 (25th October 2013) - Kim, Gi-Ae; Lim, Young-Suk; An, Jihyun; Lee, Danbi; Shim, Ju Hyun; Kim, Kang Mo; Lee, Han Chu; Chung, Young-Hwa; Lee, Yung Sang; Suh, Dong Jin
Abstract : Objective: Little is known about the long-term clinical outcome and durability of HBsAg seroclearance following nucleos(t)ide analogue (NUC) therapy in patients with chronic hepatitis B (CHB). Design: During a median follow-up period of 6 years (33 567 patient-years) of 5409 CHB patients who were initially treated with lamivudine or entecavir, a total of 110 achieved HBsAg seroclearance (0.33% annual seroclearance rate) and were included in this study. Results: Baseline alanine aminotransferase (ALT) level >5 times of upper limit of normal was associated with higher probability of HBsAg seroclearance (HR 1.80, p<0.01), while HBeAg positivity (HR 0.46, p<0.01), high HBV DNA level (log10 IU/mL; HR 0.61, p<0.01), and cirrhosis (HR 0.48, p<0.01) were inversely associated with the probability of HBsAg seroclearance by multivariable analysis. During follow-up for 287 patient-years after HBsAg seroclearance, only two patients with baseline cirrhosis developed hepatocellular carcinoma (HCC) or died (0.7% annual risk), which was of a significantly lower rate compared with propensity score-matched patients without HBsAg seroclearance (HR 0.09, p<0.01). HBsAg reversion and/or HBV DNA reversion occurred in 18 patients, most of which were transient with extremely low serum levels of HBsAg (0.05–1.00 IU/mL) and HBV DNA (17-1818 IU/mL). None required retreatment. The cumulative probability of anti-HBs seroconversion (detection of anti-HBs) at 4 years was 67.4% by Kaplan–Meier analysis. Selection for lamivudine-resistance HBV mutants during treatment was not associated with composite reversion (p=0.66). Conclusions: HBsAg seroclearance achieved after NUC treatment was associated with favourable clinical outcomes and was durable in most cases during long-term follow-up.